The effect of initial complaints and third year MRI lesion load on EDSS of multiple sclerosis patients - Guntel, Murat; Duman, Taskin; Demetgul, Ozcan (Annals of Medical Research, 2021)
Aim: We aimed to investigate the effect of initial complaints and third-year MRI lesion burden on Expanded Disability Status Scale (EDSS) of Multiple Sclerosis Patients.Materials and Methods: Patients who were admitted to the Mustafa Kemal University Faculty of Medicine Neurology clinic and diagnosed with Multiple Sclerosis according to Mc Donald diagnostic criteria were included in the study. The initial symptoms of patients, MRI lesion burden at the end of the third year, and the EDSS score were recorded retrospectively from the patient files. 74.5 % of the participants were female and 25.5 % were male. The most common initial symptoms were: Sensory symptoms, vision symptoms, pyramidal tract symptoms, and polysymptomatic. The mean age of the patients was 33.4. Mean EDSS was found to be 1.8±1.3. The total number of lesions in the brain was 14.8 ± 4.83 on average.Results: If patients compared according to the initial symptoms at the end of the third year, the highest EDSS score was at the polysymptomatic onset group, the second-highest score was at the motor onset group. The patients with the initial symptoms of motor or polysymptomatic group had a higher mean EDSS score than the patients with the initial symptoms of vision, sensorial symptoms, or cranial neuropathy. When we examine the relationship between MRI lesion load at the end of the third year and the EDSS score, there is a strong positive correlation between them. Patients who have more lesions in the brain on MRI studies have higher average EDSS scores than patients who have fewer lesions in the brain.Conclusion: We found that the initial symptoms are directly related to the third-year EDSS score and the prognosis of the disease. We found that there was a significant relationship between the number of lesions in the brain on MRI studies at the end of the third year and the mean EDSS score.
Keywords: Multiple sclerosis; MRI lesion load; EDSS; initial symptom